Component model for agent pattern-oriented design (AgentPOD) framework - Ismail, Maizatul Akmam (2010)
The explosive growth of agent system areas such as JACK (Rao and Georgeff, 1995), JADE (Bellifemine et al., 1999), Jadex (Braubach et al., 2006), and multi-agent system demand suitable agent component model that is can operate within a wide range of environments, and can evolve over time to cope with changing requirements and design. AgentPOD approach is involved in analysis and designs phase but not in implementation phase. Instead, there is a gap between design and implementation phase. An approach to easily deploy the AgentPOD into agent system is unavailable. In this project, the main focus is to identify and study an existing agent component models. The purpose of this project is to solve the limitation of AgentPOD framework with reduce the gap between design and implementation phase by using existing agent component model. An overview and meta-model of the existing agent component model such as Jadex, Cougaar, and JMX are identified. Meta-model provides the core language that is used in determine the suitable agent component model and in mapping process. The mapping process aims to motivate the use of patterns and component model at software development process that subject to deploy pattern-oriented agent system. Jadex is a FIPA specifications compliant agent development environment that gives several facilities for an easy and fast implementation. The case study “Automated Negotiation System for On-line Book Shops” is used to prove the suitability of Jadex and AgentPOD.